2018
DOI: 10.1007/s10461-018-2223-1
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Interventions for People Living with HIV and Their Families: A Systematic Review

Abstract: A variety of interventions have been tested targeting people living with HIV (PLH) and their relationships with their children. The purpose of this study was to synthesize evidence on the goals, types, scope, and outcomes of such intergenerational interventions for PLH. Randomized trials targeting PLH alone or together with their children, published in English, with an intergenerational intervention component were included in this review. Thirteen studies met eligibility criteria. The types and goals of interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
1
8
1
Order By: Relevance
“…Existing quantitative (23,(43)(44)(45)(46) and qualitative (47-49) studies on adolescent SRH needs in SSA, such as this one, demonstrate the gaps in young people's access to information and resources related to SRH, and provide the basis for the argument that sexuality education must be provided to younger adolescents. Importantly, these findings confirm research from the past decade, highlighting the magnitude of work that remains to be done to more effectively address the SRH needs of ALHIV (42,(50)(51)(52). Recent interventions highlight the importance of family engagement (29, 51, 53), peer-based approaches including peer support groups (8,52), and newer ways of engaging youth, such as mHealth (30,43,49,54).…”
Section: Discussionsupporting
confidence: 77%
“…Existing quantitative (23,(43)(44)(45)(46) and qualitative (47-49) studies on adolescent SRH needs in SSA, such as this one, demonstrate the gaps in young people's access to information and resources related to SRH, and provide the basis for the argument that sexuality education must be provided to younger adolescents. Importantly, these findings confirm research from the past decade, highlighting the magnitude of work that remains to be done to more effectively address the SRH needs of ALHIV (42,(50)(51)(52). Recent interventions highlight the importance of family engagement (29, 51, 53), peer-based approaches including peer support groups (8,52), and newer ways of engaging youth, such as mHealth (30,43,49,54).…”
Section: Discussionsupporting
confidence: 77%
“…The Cochrane Collaboration and the U.S. Institute of Medicine have endorsed that review teams must have content and methodological expertise (Bigendako & Syriani, 2018;Gøtzsche & Ioannidis, 2012;Institute of Medicine, 2011). A major strength of this study is that our contributors have undergone training in systematic review methodology and have published prior reviews (Cajita, Cajita, & Han, 2016;Han, Floyd, et al, 2018;. Additionally, most of the authors are clinicians with expertise in health promotion among populations with poor health literacy.…”
Section: Study Stregnthsmentioning
confidence: 99%
“…Long term consequences will also need to be monitored and longitudinal designs and rigorous developmentally-sensitive measurement is needed to inform the design of large-scale policies and programming for children, adolescents and youth ( 35 ). Importantly, a number of studies reported the need for intergenerational evidence, both on experiences and interventions on the mental health of children and their families ( 22 ).…”
Section: Discussionmentioning
confidence: 99%